Employing Women : A Boon for a Chemical Plant in India - Jiang, Larry (World Bank, Washington, DC, 2012)
Meghmani Organics Limited (MOL) is a chemical group located in the state of Gujarat in India. Its main products are specialty chemicals, including pigments, pesticides, and other intermediates. Prior to International Finance Corporation's (IFC's) investment, MOL had four manufacturing facilities in Gujarat, India, with about 2,000 employees. In 2008, IFC invested in MOL to build Meghmani FineChem Limited (MFL), a green field chlor-alkali plant, in Dahej, a port city in Gujarat. This smart lesson provides a snapshot of the changes that took place in MFL following IFC's recommendation for the company to employ women.